Conjugation of the Integration Potentials of the Legal Framework of the EAEU and the CIS: Current State and Prospects for Improvement - A. A. Maryshev (Евразийская интеграция: экономика, право, политика, 2023)
Aim. Give a reasoned assessment of the prospects for integration interaction between the Commonwealth of Independent States and the Eurasian Economic Union.Tasks. Tell about the beginning of the functioning of the Commonwealth of Independent States and give the structure of actually functioning bodies of the Commonwealth, substantiate the legitimacy of choosing the Eurasian Economic Union as a “hard core” of post-Soviet integration, assess the prospects of the idea of conjugation of the integration potentials of the CIS and the EAEU, tell about the joint work of the CIS and the EAEU to eliminate conflicts in their legal acts, substantiate the need for further work of the CIS and the EAEU within the framework of the emerging Greater Eurasian Partnership.Methods. To create the author’s version of the system of CIS bodies, institutional approaches were used in conjunction with structural and functional approaches. The “integration matryoshka” of the CIS — FTA — EAEU was built by the modeling method. Using the method of comparative analysis, the work of the working group on conjugation of the EAEU law and the legal framework of the CIS was analyzed. The forecasting method was used to justify the further work of the CIS and the EAEU within the framework of the emerging Greater Eurasian Partnership.Results. On the basis of specific examples, recommendations are given for combining soft and hard approaches for the development of the EAEU and the CIS with the prospect of building a Greater Eurasian Partnership in the future. Thus, the EAEU should pay attention to strengthening the supranational structure of the association, as well as to the practice of ASEAN dialogue mechanisms. At the same time, following the example of the EU, one should not create an excessive bureaucracy and exert excessive pressure on countries by interfering in their internal affairs.Conclusions. The contradiction between national and supranational interests is the most profound problem in any integration association, including the EAEU and the CIS. However, there is no universal method for solving this problem. The EAEU and the CIS should combine in their practice the experience of the EU and ASEAN as a hard and soft approach to balancing national and supranational interests.